Thomas & friends. Tales on the rails [videorecording (DVD)]. (Universal Studios Home Entertainment, 2015)
Percy's sheep escape, as Den and Dart fear working apart. James can't handle the slip coaches, while Salty's imagination has him running scared. When Percy loses control, he bravely faces his fears with a little help from his friends.